(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted to investigate the microbiological contamination of some solid food in the cafeterias and restaurants in some areas of Babil province, which included restaurants of the first class and other levels, rice, red meat, chicken meat, bread, biscuits and juices were collected for the period from November 2016 to February 2017. This study, through the microbiological analysis of the most consumed food in the cafeterias and restaurants that were studied in the areas of Alexandria and the modern village and the districts of Mahaweel, Masib and Hilla.In vitro culturing of food samples and biochemical tests of bacteria on culture media, Escherichia coli was found, Staphylococcus epidermidis, Staphylococcus aureus, Salmonella typhi, Shigella dysentriae and some fungi on their culture media. The study also showed that cooked foods loaded by alower germs than fresh foods. The results also showed that the foods used in restaurants are less than a microbial load of cafeterias. This study highlights the level of microbial content found in different foods available in cafeterias and restaurants.